The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.21203/rs.3.rs-2310883/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parametric analysis and quantitative study on the influence of structure cluster on ground motion

Abstract: This study conducted the parametric and quantitative analysis of the influence of soil-structure cluster interaction (SSCI) on ground motion. Based on the results of the shaking table test and numerical simulation, the changes in the characteristics of ground motion with the alterations of multiple factors are explored via wavelet packet decomposition. The results indicated that: (a) structure cluster reduces the site eigenfrequency, thereby amplifying the low-frequency components of ground motion and attenuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…In general, the ground motion slightly weakens from the center of the structure cluster radially and this variation becomes more significant with a higher-frequency seismic excitation when only the effect of structural relative position is considered. 26 It is explained by the fact that the variation of the radiation damping and the dispersion of high-frequency components within heterogeneous mediums. This effect is negligible for the seismic response of the structural principal mode.…”
Section: Discussion Of Factors Excluding In Modelling Sscimentioning
confidence: 99%
See 4 more Smart Citations
“…In general, the ground motion slightly weakens from the center of the structure cluster radially and this variation becomes more significant with a higher-frequency seismic excitation when only the effect of structural relative position is considered. 26 It is explained by the fact that the variation of the radiation damping and the dispersion of high-frequency components within heterogeneous mediums. This effect is negligible for the seismic response of the structural principal mode.…”
Section: Discussion Of Factors Excluding In Modelling Sscimentioning
confidence: 99%
“…According to Refs. 25 and 26, it can be found that the disturbance of the adjacent structure to the target structure presents a monotone attenuation with the increase in the foundation spacing, and the disturbance radius is related to the structural period and shear wave velocity of subsoil. Therefore, the range of the coefficient ( η ) is defined from 0 to 1 as shown in Equation (), and its value is attenuated by the increase in the spacing between the target structure and the adjacent structure.…”
Section: Influential Parameters On Sscimentioning
confidence: 99%
See 3 more Smart Citations